Growth regulation and off-season flowering through night breaks in Chrysanthemum morifolium Ramat cv. Anmol (Bangladesh Journal of Botany, 2019)
The photoperiodic night interruption to schedule efficient flowering time in Chrysanthemum morifolium Ramat cv. Anmol according to demand of its flowers in the market was monitored. The influence of six night interruption treatments i.e. control,